Politics of Law on Protection to Folklore in a Regional Autonomy Perspective: Rights for Indigenous People - Dilaga, Auria Patria (JILS (Journal of Indonesian Legal Studies), 2017)
The study of political law on protection of folklore with the perspective of regional autonomy is expected to be realized ideal protection. The problem in this research is why folklore needs to be protected in the perspective of regional autonomy and how the political law of folklore protection in the regional autonomy perspective. This research approach method using normative juridical approach method. The result of this research is folklore needs to be protected because it is part of the wealth of the Republic of Indonesia. Folklore needs to be protected in the perspective of regional autonomy because it is a work that was born and developed and preserved in their respective regions. The politics of law of folklore protection in the perspective of regional autonomy is by making technical implementation policy up to the level of local regulations for the benefit of folklore protection, one of them with the policy of inventory. The conclusions and suggestions in the research are folklore is a human work that must be protected especially in the perspective of regional autonomy and it is advisable to immediately pass a regulation on the protection of folklore.